Meanings of “Ubiquitous Learning” - Burbules, Nicholas C. (Education Policy Analysis Archives, 2014)
In an era when people can carry the Internet in their pocket, teaching and learning must be reconsidered. The increased use of handheld and portable devices, along with pervasive wireless networking, means that structured learning opportunities are becoming an “any time, anywhere” enterprise. We talk about this shift in terms of ubiquity: the traditional divide between formal and informal contexts of learning is breaking down. Technological as well as social, cultural, and institutional changes mean that learning is a continuous possibility. The essay concludes with some brief observations about the implications of these changes for the professional training and development of teachers.